Agrobacterium-mediated transformation of Hevea brasiliensis with apple cDNA encoding sorbitol-6-phosphate dehydrogenase - Jayasree P K; Divya S; Supriya R; Thulaseedharan A (Rubber Science, 2015)
The increasing demand of natural rubber abd land unavailability in traditional regions has been resulted the cultivation of rubber in non-traditional regions. However, the severe agro-climatic conditions in non-traditional regions adversely affected growth and yield of rubber. In this context, scope for the introduction of genes conferring tolerance to abiotic stresses is of paramount importance and hence the study was undertaken. Embryogenic callus derived from immature anther of Hevea brasiliensis, clone RRII 105 was used as the target tissue for genetic transformation. Kanamycin sensitivity to embryogenic callus was examined by kill curve test and medium with 100 mgL-1 kanamycin completely suppresses the growth of untransformed callus and was selected as the suitable concentration for selection of transformants. Addition of ABA was found to be beneficial for embryogenesis and maximum embryo induction was obtained with 2.0 mgL-1. Among various levels of sucrose (2-10;), 4 per cent sucrose enhanced embryo induction efficiency and gradually decreased by higher levels. Mature embryos get germinated and converted into plantlets. GUS histochemical assay revealed expression of uidA gene in transformed callus and embryos which was evidenced by the intense blue colour. Polymerase chain reaction confirmed the presence of S6PDH, uidA and nptII genes in transformed callus and embryos. The transgenes were also detected in plasmid DNA (positive control), but absent in untransformed callus (negative control).
Keywords: Agrobacterium tumefaciens; Genetic transformation; GUS histochemical assay; PCR analysis; Sorbitol-6-phosphate dehydrogenase gene